Growth, development and yield responses of sorghum to water deficit stress, nitrogen fertilizer, organic fertilizer, and planting density - Rethman, N.F.G. (University of Pretoria, 2013)
Thesis (PhD (Agronomy))--University of Pretoria, 2004.